Otoritas Konten Instagram taulebih.id dalam Memberikan Edukasi dan Pendampingan Konseling Terhadap Pendidikan Seksual Basis Islam - Fitroti, Livi Husnia Aidatul; Ahmad Fauzi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Abstract: This paper tries to analyze the literacy and counseling assistance movement in the mass media regarding Islamic-based sexual education education on the @taulebih.id instagra account. sexual education is currently information that is widely campaigned for but is still taboo to talk about. The issues and problems of the discourse continue to grow but the right information about it is still lacking. The @taulebih.id account then has the vision to provide educational assistance in the form of information about Islam-based sexual education. This paper will explain how the form of assistance carried out by the @taulebih.id account in providing public awareness about Islam-based sexual education. This discourse then becomes important to study because in the freedom of opinion in the digital space makes a prolonged skeptical rotation of the information processed, especially in the era of information about sexual education that is increasingly wild and free. Explicitly this article will try to find answers to several questions that arise, including: How is the assistance provided by the @taulebih.id account in providing Islam-based sexual education? What kind of authority is built on the @taulebih.id account in providing trust and awareness of the information uploaded. The results of this discourse show that the dynamics of the authority of the @taulebih.id account in providing information and assistance in Islamic-based sexual education education are exemplified by producing content related to it, strengthening authority by providing references. In every content production, and provide direct assistance through Islamic-based sexual education classes and counseling both online and offline. The majority of information posted by @taulebih.id is about Islamic-based sexuality education